2011
DOI: 10.1007/s11661-011-0773-1
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-Growth Transition and Homogenous Nucleation Undercooling of Bismuth

Abstract: The cross-sectional and surface morphologies of highly undercooled bismuth samples are investigated by optical microscopy and scanning electron microscopy. It is found that the grain morphology can be classified into three types. When the undercooling is less than 49 K (49°C), flaky grains with pronounced edges and faces are arranged parallel to each other, showing the feature of lateral growth. When the undercooling is over 95 K (95°C), refined equiaxial grains with several smooth bulges on the surface of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This can explain the direct formation of Nb 5 Si 3 dendrites in EBSM alloy, which is an indication of continuous growth. Such microstructural transition from faceted to non-faceted growth enabled by a larger kinetic undercooling has been observed in the solidification of some other materials with high entropy of fusion like primary Mg 2 Si in Al-Mg 2 Si alloys [15], silicon [34,35], bismuth [17], germanium [36] and Al 2 O 3 [37], etc. It is interesting to find that the rapidly solidified β-Nb 5 Si 3 phases can transform to the α-Nb 5 Si 3 phases via annealing due to its better thermal stability at room temperatures, indicated by the Nb-Si binary phase diagram [38].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This can explain the direct formation of Nb 5 Si 3 dendrites in EBSM alloy, which is an indication of continuous growth. Such microstructural transition from faceted to non-faceted growth enabled by a larger kinetic undercooling has been observed in the solidification of some other materials with high entropy of fusion like primary Mg 2 Si in Al-Mg 2 Si alloys [15], silicon [34,35], bismuth [17], germanium [36] and Al 2 O 3 [37], etc. It is interesting to find that the rapidly solidified β-Nb 5 Si 3 phases can transform to the α-Nb 5 Si 3 phases via annealing due to its better thermal stability at room temperatures, indicated by the Nb-Si binary phase diagram [38].…”
Section: Discussionmentioning
confidence: 61%
“…For rapidly solidified alloys, the growth mode of thermodynamics-controlled faceted phases, may be altered concomitantly, e.g., the transition from faceted to nonfaceted growth of intermetallic phases with high entropy of fusion [14,15]. The mechanism behind this morphology transition is mainly due to the change in the solid/liquid interface structures and roughness [16,17]. Previous literature [6,12,18] has reported that beneficial microstructure modification of Nb-Si based alloys is enabled by rapid solidification, resulting in improvements of oxidation resistance and fracture toughness.…”
Section: Introductionmentioning
confidence: 99%